Study and analysis of edible bird nest's (EBN) microstructure and the basic parameters (soaking time, temperature and frequency) for the cleaning purpose - Moh, Wei Soon (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Bird nest is secreted from several different species of swallow salivary. There are only two out of twenty four species that can only be deemed as 'edible' which are white-nest swiftet (Aerodramus Fuciphogus) and black-nest (Aerodramus Maximus). Nowaday, there are plenty of nutrient analysis works on edible bird nest (EBN).